Determinación del régimen de riego mediante el uso de tensiometros en el cultivo de nabo brassica rapa subsp rapa bajo invernadero - Espinoza Piñaloza, Adriana Lisseth (2018)
To determine the optimal time of irrigation, it is advisable to use a method that supports the need to irrigate, since continuous information can be obtained in real time, even changes in soil moisture status provided that it is correctly installed in the effective root zone of the soil. Culture and this method isdone using tensiometers. An irrigation plan implies the maximum and minimum knowledge of the soil that guarantees the yields of a crop the level of moisture retention rather than in the soil The maximum moisture retention level of a soil (field capacity) corresponds to a potential matric that is between 20cb. The research was carried out under greenhouse in the research area of the irrigation and drainage chair of La Granja "Santa Inés" belonging to the Academic Unit of Agricultural Sciences of the Technical University of Machala, where the following objectives were proposed 1.Determine the irrigation regime through tensiometers, to optimize the water resource; 2. Build the humidity retention curve, with the use of tensiometer, to program the risks; three. Determine the optimal matrix potential through the tensiometers, to effect the irrigation in the culture of turnipThey are normal if a period of a day or two is considered after an irrigation, although if they persist they indicate an excess of humidity, generally due to too abundant watering, readings of 20 cb: they indicate that the humidity is available to the plant with a minimum effort. With drip irrigation, it is generally tried to maintain the readings within this range, when the tensiometer is placed at a distance of approximately 10cm from the dropper, readings of 30 cb in this range of readings a good oxygenation of the roots is ensured. The analysis of variance (ANOVA), gave as a result that if there was statistical difference for the treatments in net biomass, number of leaves, moisture content of the aerial part of the turnip, moisture content of the root. At the end of the investigation it can be pointed out that the best tension is that of the treatment T2 that presented significantly better results in the variables net biomass and number of leaves, since it is better to apply a sheet of water to 20cb where the water costs will be better than those of 10cb as opposed to the moisture content of the part aerial and the root which were the T1el treatment that presented greater significance to that higher water content is the turgor of the plants